2012
DOI: 10.1021/ol301112m
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Synthesis of α-Stereogenic γ-Keto Esters via Formal Umpolung

Abstract: A feasible method has been developed for the enantioselective synthesis of α-stereogenic γ-keto esters. By employing nitro(phenylsulfonyl)methane as an acyl anion equivalent, the integrated Michael addition reaction-oxidative methanolysis protocol allows the preparation of various γ-keto esters with high optical purities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…188,191 The addition of malononitrile to a chalcone derivative in the presence of a quinine-derived bifunctional thiourea tertiary amine ( 21 ) as a catalyst results in compound 15 . The mechanism of the Michael addition of malononitrile to chalcones has also been examined using theoretical calculations.…”
Section: Chemical Reactions Related To Michael Acceptorsmentioning
confidence: 99%
“…188,191 The addition of malononitrile to a chalcone derivative in the presence of a quinine-derived bifunctional thiourea tertiary amine ( 21 ) as a catalyst results in compound 15 . The mechanism of the Michael addition of malononitrile to chalcones has also been examined using theoretical calculations.…”
Section: Chemical Reactions Related To Michael Acceptorsmentioning
confidence: 99%
“…The resulting g-keto esters are produced in moderate yields and high enantioselectivity (Scheme 62). [137] Enantioselective conjugate additions of nitromethane 124 to chromenes were reported by Wang et al achieving very good results. [138] Again a low diastereoselectivity is observed by deployment of other nitroalkanes (Scheme 63).…”
Section: Prakash Et Al Applied Nitro-(phenylsulfonyl)-methane 130mentioning
confidence: 99%
“…The alkylation is followed by an oxidative methanolysis via a two‐step one‐pot protocol. The resulting γ‐keto esters are produced in moderate yields and high enantioselectivity (Scheme ) 137…”
Section: Henry Reaction and Related Reactionsmentioning
confidence: 99%
“…Seminal work by Hu and co‐workers showed that α‐fluorodi(benzenesulfonyl)methane, (PhSO 2 ) 2 CFH, reacts with enones faster than di(benzenesulfonyl)methane, (PhSO 2 ) 2 CH 2 . Similarly, the urea‐catalyzed reactions between α‐fluoro‐α‐nitro(benzenesulfonyl)methane and chalcones are also more rapid than those of nitro(benzenesulfonyl)methane ,. Furthermore, despite that the nucleophilic addition of (PhSO 2 ) 2 CFLi to benzaldehyde leads to the corresponding alcohol in high yield, no adduct was obtained in the reaction with (PhSO 2 ) 2 CHLi or (PhSO 2 ) 2 CClLi under similar reaction conditions .…”
Section: Figurementioning
confidence: 99%